Ohmic contact formation to heavily boron-doped p+ diamond prepared by hot-filament chemical vapor deposition. Issue 51 (20th June 2016) - Ohmagari, Shinya; Matsumoto, Takeshi; Umezawa, Hitoshi; Mokuno, Yoshiaki
ABSTRACT: Diamond-based rectifiers are promising devices for the development of next-generation power electronics. However, presented device structures limit current operation as low as tens A, which hampers diamond from real industrial applications. One of the critical issues is poor availability of conductive (low-resistivity) substrates which can be used for vertical-type devices for high-output operations. Recently, we have successfully fabricated heavily boron-doped (p+) low-resistivity diamond by hot-filament chemical vapor deposition (HFCVD). Resistivity was monotonically decreased to 1.2 mΩcm with amount of doped boron. In this study, to further investigate potentials for electric applications, contact resistance between metal/p+ diamond was evaluated by transmission line model (TLM). From the current-voltage characteristics, low specific contact resistance of ∼10 −7 Ωcm 2 was demonstrated.